2002
DOI: 10.1097/00005537-200206000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Maxillary Sinusitis of Dental Origin: Is External Surgical Approach Mandatory?

Abstract: Endoscopic approach to chronic maxillary sinusitis of dental origin is a new, reliable method associated with less morbidity and lower incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 4 publications
2
90
2
7
Order By: Relevance
“…2,3,7,8,11 A combined approach, trans nasal and trans-oral was also described. 9 Various other studies refer to the use of endoscopy for removal of other foreign bodies including amalgam and teeth roots amongst others. [9][10][11] A single article com pares the complications of this alternative to the classic Caldwell-Luc procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,7,8,11 A combined approach, trans nasal and trans-oral was also described. 9 Various other studies refer to the use of endoscopy for removal of other foreign bodies including amalgam and teeth roots amongst others. [9][10][11] A single article com pares the complications of this alternative to the classic Caldwell-Luc procedure.…”
Section: Discussionmentioning
confidence: 99%
“…9 Various other studies refer to the use of endoscopy for removal of other foreign bodies including amalgam and teeth roots amongst others. [9][10][11] A single article com pares the complications of this alternative to the classic Caldwell-Luc procedure. 12 The sublabial (labial vestibular) inci sion results in signifi cant postoperative discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to rhino-sinusitis, most cases of OMS are still treated by a Caldwell-Luc type of surgery. However, several studies were published, reporting results of FESS for treatment of chronic odontogenic sinusitis (Lopatin et al, 2002;Costa et al, 2007;Andric et al, 2010;Albu & Baciut, 2010;Hajiioannou et al, 2010), which will be discussed in details later in this chapter.…”
Section: Functional Endoscopic Sinus Surgery For Treatment Of Odontogmentioning
confidence: 99%
“…Recently, several authors reported results of FESS for treatment of chronic odontogenic sinusitis (Lopatin et al, 2002;Costa et al, 2007;Andric et al, 2010;Albu & Baciut, 2010;Hajiioannou et al, 2010). Although there were some technical differences, all studies have reported essentially the same surgical procedure, comprising middle meatal antrostomy, access to the maxillary sinus through enlarged natural sinus ostium and endonasal approach for removal of intra-antral foreign bodies, such are root tips and dental implants.…”
Section: Literature Datamentioning
confidence: 99%
See 1 more Smart Citation